Factors Affecting the Growth of the Agricultural Sector in Langkat Regency - Azulaidin; Anwar (Budapest International Research and Critics University, 2020)
Regional economic development has an important role in the success of development at the national level. The state of the national economy is structured by the state of the regional economy. Seeing the condition of Indonesia which has a large area and a relatively large number of provinces, the availability of infrastructure and physical capital has an important role in increasing economic growth. Production infrastructure can be provided by both the government and the private sector. The government as the main development agent has a big responsibility in providing infrastructure and adequate capital for both public and private interests. In addition, the availability of labor as a human resource in addition to nature, capital and technology also has an important role for the economy. The agricultural business in Langkat Regency in 2018 contributed to the formation of a total GRDP of 35.06 percent, a decrease from 2016 which was 35.61 percent. Meanwhile, the growth rate has slowed down from 5.33 percent in 2017 to 4.76 percent in 2018. Factors that affect growth in Langkat Regency are land area, capital accumulation, population and labor growth, technological advances, exports and agricultural budgets that affect the growth rate of the agricultural sector.